The Effect Of Audio Visual Media On The Ability To Count Of Kindergarten - Yessi Rifmasari; Riwayati Zein; Villa Anggraini (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The problem of this research is based on the low ability of children in numeracy when using the number symbol and matching numbers with the number symbol in kindergarten.This study aims to improve the ability to count children at the age of 5-6 years through audio visual media of kindergarten. This type of research is an experimental study nonequivlent control group design. The research population of all children aged 5-6 years while the selected research samples were grade B2 and B4. Sampling techniques using purposive sampling techniques, this study uses the t-test formula preceded by the analysis requirements test in the form of normality test and homogeneity test. Based on the analysis of data obtained from the test results of data from the sample class that is normal and homogeneous distribution, further hypothetical tests with t-test showed obtained . thitung > ttabel is 3,186>2,042 and sig. > sig.a (0.003